PARP Inhibitors in Ovarian Cancer - Mittica, Gloria; Ghisoni, Eleonora; Giannone, Gaia; Genta, Sofia; Aglietta, Massimo; Sapino, Anna; Valabrega, Giorgio (Recent Patents on Anti-Cancer Drug Discovery, 2018)
Background: Treatment of Epithelial Ovarian Cancer (EOC), historically based on surgery and platinum doublet chemotherapy, is associated with high risk of relapse and poor prognosis for recurrent disease. In this landscape, the innovative treatment with PARP inhibitors (PARPis) demonstrated an outstanding activity in EOC, and is currently changing clinical practice in BRCA mutant patients. Objectives: The study aimed to highlight the mechanism of action, pharmacokinetics, clinical activity, indications and current strategies of development of Olaparib, Niraparib, Rucaparib, Talazoparib and Veliparib, the 5 most relevant PARPis. Methods: We performed a review on Pubmed using 'ovarian cancer' and the name of each PARPi (PARP inhibitor) discussed in the review as Medical Subject Headings (MeSH) keywords. The same search was performed on “clinicaltrial.gov” to identify ongoing clinical trials and on “google. com/patents” and “uspto.gov” for recent patents exploring PARPIs in ovarian cancer. Results: Olaparib, Niraparib and Rucaparib are already approved for the treatment of recurrent EOC and their indications are partially overlapping. Talazoparib and Veliparib are promising PARPis, but currently under investigation in early phase trials. Several studies are evaluating PARPis in monotherapy or in associations, in a wide range of settings (i.e. first line, neoadjuvant, platinum-sensitive and resistant disease). Conclusion: PARPis are valuable options in patients with recurrent ovarian cancer with promising activity in different stages of this disease. Further studies are required to better define optimal clinical settings, predictors of response beyond BRCA mutations and strategies to overcome secondary resistance of PARPis therapy in EOC.
Keywords: ovarian cancer